Textos de divulgação científica: leitura, produção e divulgação de atividades didáticas no espaço do estágio supervisionado em física - Correia, Daniele (2016)
Researches in Sciences Education are aware of the importance of reading Popularization Science Texts (TDC) in order to form reading subjects and these texts potentialities in the teaching and learning process of scientific contents. Thus, the present article is structured in the format of three scientific texts: The first text Readings of Popularization Science Texts done by undergraduate students in the Supervised teacher s practice in Physics; The second text Reading and Arguing: Potential Use from Popularization Science Texts in Middle of Physical Education in High School; The third text Study of Sound Waves in an Educational Activity using a Popular Science Text. These texts contemplate research developed between 2013 and 2015 in Teaching Management in the Physics Course at Universidade Federal de Santa Maria when two trainees, under the advice and supervision of the author of this present thesis, developed teaching and research activities involving TDC. The present study has the aim of investigating readings about (teaching dimension) and about the use of TDC (research dimension) associated to reading strategies carried out by teacher trainees. Within the teaching dimension, the trainees produced and implemented activities employing TDC associated to reading strategies in their class planning and their taught classes (Text 1). It was observed that in the class planning stages the TDC made by the trainees employed paraphrase characterized by the search of information, and the didactic function attributed to TDC was in the realm of Physics contents. However, during the trainees classes, multi-level readings were valued so that text-pretext was the reading strategy developed and the discourse appropriated by the trainees tended to be controversial. Regarding the didactic role of TDC in classes, it was observed that these, besides being employed to teach Physics, promoted the development of abilities related to oral and written expressions on the part of learners, improving not only the articulation between physics contents and learners daily life, but foremost helped the trainees to reflect on meanings and ends of Physics contents teaching. Regarding the research dimension, the trainees produced (together with their advisors) scientific texts (Texts 2 and 3) that tackled their own readings on the use of TDC experienced through the use of implemented activities done during their taught classes. Along these manuscripts, the authors assure that the activities with TDC associated to reading strategies contribute significantly for the teaching and learning process of scientific contents and for the forming of student readers. Finally, it has to be pointed out that the trainees evaluated the practices of reading, writing, teaching and learning positively together with research with TDC developed in class management in Physics; besides, they claimed that those activities were of extreme importance to their personal and professional improvement.